PENGARUH LATIHAN RELAKSASI OTOT PROGRESIF DIIRINGI MUROTTAL AL – QUR’AN TERHADAP PERUBAHAN NILAI GULA DARAH PADA PASIEN DIABETES MELITUS TIPE II - Nisa, Alifah Khaerun; Riyana, Asep; Kusmiyati, Kusmiyati; Badriah, Siti (Jurnal Medika Cendikia, 2024)
The high incidence of Diabetes Mellitus in the Mangkubumi Community Health Center working area and the difficulty of controlling blood sugar are the main problems that must be addressed. This study aims to determine the characteristics, changes and influence of Progressive Muscle Relaxation Exercises accompanied by Murottal Al-Qur'an on Changes in Blood Sugar Values in Type II Diabetes Mellitus patients. This research used Quasy Experimental One Group Pretest & Post-test using purposive sampling technique with a sample size of 38 people in the intervention group. The tool used is an Accu Check Glucometer. The statistical test used is the paired sample t-test. There is a difference in the average blood sugar value before and after being given Progressive Muscle Relaxation Exercises accompanied by Murottal Al-Qur'an with a value of 0.000. There is an effect of Progressive Muscle Relaxation Exercise intervention accompanied by Murottal Al-Qur'an on changes in blood sugar values in patients with type II diabetes mellitus.